Resolution of the Board of Supervisors of Ventura County, to Reaffirm its Position on the Acquisition of Oxnard Air Force Base, and to Expedite the Transfer of Ownership from the Federal Government to the County of Ventura County - Thomas Laubacher::::::
A resolution discussing the acquisition of the former Oxnard Air Force Base and the restrictions that are to be implemented.